Isolation of Keratan Sulfate Disaccharide-branched Chondroitin Sulfate E from Mactra chinensis - Kyohei Higashi; Toshihiko Toida (Bio-Protocol, 2017)
Glycosaminoglycans (GAGs) including chondroitin sulfate (CS), dermatan sulfate (DS), heparin (HP), heparan sulfate (HS) and keratan sulfate (KS) are linear, sulfated repeating disaccharide sequences containing hexosamine and uronic acid (or galactose in the case of KS). Recently, a keratan sulfate (KS) disaccharide [GlcNAc6S(β1-3)Galactose(β1-]-branched CS-E was identified from the clam species M. chinensis. Here, we report the isolation protocol for KS-branched CS from M. chinensis.